ON STAUDE' S NEW GENERIC NAMES FOR AGARICS - M. A. DONK (BRIN Publishing (Penerbit BRIN), 1954)
The author concludes that the generic names for agarics first introduced by Staude (1857) have been validly published.When I drew attention to Staude's forgotten